2009
DOI: 10.1007/s10165-009-0177-x
|View full text |Cite
|
Sign up to set email alerts
|

Tight control is important in patients with rheumatoid arthritis treated with an anti-tumor necrosis factor biological agent: prospective study of 91 cases who used a biological agent for more than 1 year

Abstract: The purpose of this study is to identify the factors that require arthroplasty due to the progression of joint destruction, even when an anti-tumor necrosis factor (TNF) biological agent is used for rheumatoid arthritis (RA). Among 91 cases that used the anti-TNF biological agent for more than 1 year, two groups of 21 cases that resulted in arthroplasty (surgery group) and 70 cases that did not result in arthroplasty (non-surgery group) were compared and examined. When the anti-TNF biological agent was first a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Goekoop-Ruiterman et al [ 46 ] and Schipper et al [ 5 ] previously compared a tight control treatment with usual care and showed a better response after 1 year for tight control. Other data suggest that tight control may improve longterm functional disability [ 47 ], and reduce the need for joint surgery among patients with RA treated with biological agents [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goekoop-Ruiterman et al [ 46 ] and Schipper et al [ 5 ] previously compared a tight control treatment with usual care and showed a better response after 1 year for tight control. Other data suggest that tight control may improve longterm functional disability [ 47 ], and reduce the need for joint surgery among patients with RA treated with biological agents [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant correlation was found between tight disease control (DAS28 < 2.6) and functional disability score [using the Japanese version of the Health Assessment Questionnaire (HAQ)]; tight control was significantly associated with improving functional capability. A second study in patients receiving anti-TNF treatment for ≥ 1 year found that mean DAS28 (including a measure of CRP levels) among patients who did not require joint surgery (n = 70) was significantly lower (p < 0.001) than among patients who required joint surgery (n = 21) 21 . The authors concluded that tight disease control was important in reducing the need for joint surgery among patients receiving biologic therapy.…”
Section: Advantages Of Tight Control: Evidence From Clinical Trialsmentioning
confidence: 98%
“…Other recent data suggest that tight control may improve longterm functional disability 20 and reduce the need for joint surgery among patients with RA treated with an anti-tumor necrosis factor (TNF) agent 21 . Tanaka and coworkers 20 followed 2775 patients in an observational cohort study for whom 3 years of data were available.…”
Section: Advantages Of Tight Control: Evidence From Clinical Trialsmentioning
confidence: 99%
“…The incidence of total joint replacement decreases with time, likely due to advances in RA treatment with MTX and biologic DMARDs (23)(24)(25)(26)(27). A previous study suggested that in order to inhibit the need for total joint replacement in patients treated with TNF inhibitors, it is important to maintain tight control over RA activity (28). This study investigated the effects of concomitant MTX on the incidence of large joint replacement in patients with RA treated with TNF inhibitors.…”
Section: Discussionmentioning
confidence: 98%